Ageing Asia's Looming Pension Crisis - Donghyun Park (Asian Development Bank (ADB), 2009)
Due to population aging, weakening of family-based support, and other factors, old-age income support is becoming an issue of growing importance throughout Asia. This is especially true in East Asia and Southeast Asia where the demographic transition is already well under way. This paper provides a broad overview of the current state of the pension systems in People's Republic of China, Indonesia, Republic of Korea, Malaysia, Philippines, Singapore, Thailand, and Viet Nam; diagnoses the pension systems; and identifies their major structural weaknesses. Key systemic failures were found to be low coverage, inadequate benefits, lack of financial sustainability, and insufficient support for the elderly poor. The paper concludes with some specific policy directions for pension reform to strengthen the capacity of Asian pension systems in delivering economic security for the looming large and growing army of the elderly in the region.
hdl:11540/1819
Keywords: H55; 330; Pension; social security; Asia; Alternde Bevölkerung; Altersvorsorge; Systemvergleich; China; Indonesien; Südkorea; Malaysia; Philippinen; Singapur; Thailand; Vietnam